Bunga Bank Perspektif Fazlurrahman dan Wahbah az-Zuhaili - Rumsida, Sya'baniyah (2016)
Ribā and interest were two terms those could not be separated in the study of contemporary economics. Now the problem is that when definition of ribā is faced with definition of interest, in one side the interest contains elements of ribā and in the other side interest is an economic pace of banks in order to increase prosperity. Bank encountered many controversies in term of the legal status of interest, especially Muslim community around the world who often wonder whether the interest halal, haram or subhat. This became thought for the ulamas and experts of Islamic law in solving the legal status of interest. This research used library research by collecting data using the method of documentation that retrieved and collected personage data from books, journals, newspapers at the library. The author used qualitative descriptive method that was a sentences to clarify a person's meaning in order to obtain a conclusion. The author also used content analysis. Content analysis is a research analysis technique to draw conclusions that was replicable and valid data that notice the context. Wahbah az-Zuhaili contended that practically interest became an advantage that was allowed on economic system, as the value of the time for compensation that was considered the same formulation as ribā and that was forbidden due to the additional elements that was required. Different from Wahbah az-Zuhaili, Fazlurrahman criticized the definition of ribā as addition to the principal capital. The prohibition of of ribā was due to create injustice.